Maternal per- and poly-fluoroalkyl substances exposures associated with higher depressive symptom scores among immigrant women in the Chemicals in Our Bodies cohort in San Francisco. (February 2023) - Aung, Max T.; Eick, Stephanie M.; Padula, Amy M.; Smith, Sabrina; Park, June-Soo; DeMicco, Erin; Woodruff, Tracey J.; Morello-Frosch, Rachel
Highlights: Depressive symptom scores are higher among immigrant compared to US born women. PFOS and Me-PFOSA-AcOH are associated with higher depressive symptom scores. Cumulative PFAS mixture is associated with higher depressive symptom scores. Associations with depressive symptom scores are amplified among immigrant women. Abstract: Background: Exposure to per- and poly-fluoroalkyl substances (PFAS) remains an important public health issue due to widespread detection and persistence in environmental media, slow metabolism in humans, and influences on physiological processes such as neurological signaling. Maternal depression is highly prevalent during pregnancy and postpartum and is potentially sensitive to PFAS. The health risks associated with PFAS may be further amplified in historically marginalized communities, including immigrants. Objective: Evaluate maternal concentrations of PFAS in association with depression scores during pregnancy and whether effects differ between US born and immigrant women. Methods: Our study sample included 282 US born and 235 immigrant pregnant women enrolled in the Chemicals in Our Bodies prospective birth cohort based in San Francisco, CA. We measured 12 PFAS in serum samples collected in the second trimester and depressive symptom scores were assessed using the Center for Epidemiologic Studies Depression Scale. Associations were estimated using linear regression, adjusting for maternal age, education, pre-pregnancy body mass index, and parity. Associations with a PFAS mixture were estimated using quantile g-computation. Results: In adjusted linear regression models, a twofold increase in two PFAS was associated with higher depression scores in the overall sample, and this association persisted only among immigrant women ( β [95 % confidence interval]: perfluorooctane sulfonic acid (2.7 [0.7–4.7]) and methyl-perfluorooctane sulfonamide acetic acid (2.9 [1.2–4.7]). Quantile g-computation indicated that simultaneously increasing all PFAS in the mixture by one quartile was associated with increased depressive symptoms among immigrant women (mean change per quartile increase = 1.12 [0.002, 2.3]), and associations were stronger compared to US born women (mean change per quartile increase = 0.09 [-1.0, 0.8]). Conclusions: Findings provide new evidence that PFAS are associated with higher depression symptoms among immigrant women during pregnancy. Results can inform efforts to address environmental factors that may affect depression among US immigrants.